Changes in metabolic parameters in patients with severe mental illness over a 10-year period: A retrospective cohort study. (January 2017) - Heald, Adrian H; Martin, Julie L; Payton, Tony; Khalid, Luma; Anderson, Simon G; Narayanan, R Prakash; De Hert, Marc; Yung, Alison; Livingston, Mark
Background: Diabetes, obesity and metabolic syndrome are highly prevalent in patients with severe mental illness and can impose a major physical health burden. Objective: To determine how anthropometric and metabolic features changed over time in a retrospective cohort of people with Severe Mental Illness living in Cheshire, UK. Methods: In all, 1307 individuals on the severe mental illness Register were followed up between 2002 and 2012 in UK general practice. Subjects were identified through a pseudanonymised search of general practice registers. Results: Baseline body mass index was 28.6 kg/m 2 increasing to 31.0 at 10-year follow-up ( r 2 = 0.84; p = 0.0002). There was a significant increase in fasting blood glucose from 5.72 to 6.79 mmol/L ( r 2 = 0.48; p = 0.026). Correspondingly, there was a strong positive univariate relation between increase in body mass index and fasting blood glucose ( r 2 = 0.54; p < 0.0001) taking into account all measurements. Fasting blood glucose also increased slightly with age ( p = 0.028). With increasing use of statins, total cholesterol fell from 4.5 to 3.9 mmol/L ( r 2 = 0.88; p = 0.0001), as did low-density lipoprotein cholesterol from 3.43 to 2.35 mmol/L ( r 2 = 0.94; p = 0.0001). In multivariate models, adjusting for age, gender, smoking and blood pressure, each unit increase in body mass index (odds ratio = 1.07 [1.01, 1.13]; p = 0.031) and triglycerides (odds ratio = 1.28 (1.06, 1.55); p = 0.009) was independently associated with an increased risk of having type 2 diabetes. Conclusion: Increasing body mass index relates to increasing rates of dysglycaemia over time. Measures to encourage weight reduction should be key strategies to reduce dysglycaemia rates in severe mental illness. Prescribing statins may have been effective in improving the lipid profile in this group.